Penerapan Platform Visualisasi dan Analisis Trafik Jaringan menggunakan Elastic Stack - Shafira Aulia Indrarto; Achmad Basuki (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Monitoring system is a system that aims to monitor activities on network devices. Monitoring is needed to monitor any problems that have the potential indication to disrupt the internet network. A method that can be used to monitor the network is to use the Elastic Stack. In this final project, Elastic Stack will be applied to monitor network traffic by providing a visualization of the existing network traffic data and then analyzing the traffic data. The main component of this system is a server in which the Elastic Stack components have been configured, there are Packetbeat, Elasticsearch and Kibana. The process for visualizing and analyzing network traffic begins with data collection, data transmission, data processing and data visualization on the dashboard. In the data collection process, the data used is sample data from network traffic at Brawijaya University which is obtained using TCPdump. Next, the sample data will be sent to Elasticsearch by Packetbeat to be stored in the database and indexed. The indexed data will be grouped then into certain fields to indicate what information is contained in the sample data. In these fields, visualizations in the form of pies, charts and graphs will be displayed on the Kibana Dashboard based on data stored.